Exploration on Cultivating Students’ Innovative Ability in Flash Animation Teaching - Gao, Yongli (Journal of Education and Educational Technologies, 2023)
Flash animation creation has strong practicality and artistry, which is very conducive to stimulating students' interest in learning, cultivating students' innovative ability, and how to inspire students, carry out bold creativity, and finally complete a specific project. This paper proposes to create an innovative environment, reform teaching methods, establish a flexible assessment mechanism, and carry out appropriate competition activities to comprehensively improve students' independent innovation ability.